Integration of Gamification in Career Guidance to Improve Students' Work Skills in the Digital Era: A Systematic Literature Review - Nurul Fazria; Nur Hisna Daniati; Ifdil Ifdil; Daharnis Daharnis (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The integration of gamification into career guidance services offers an innovative approach to addressing the challenge of student work-readiness in the digital era. This systematic literature review explores the potential of gamification to enhance students' employability skills through career guidance interventions. Following PRISMA 2020 guidelines, the study analyzed 12 peer-reviewed articles from Scopus and Google Scholar databases published between 2020-2025. The findings reveal that gamification elements, including simulations, serious games, and metaverse-based environments, effectively develop both hard skills (technical competencies, financial literacy) and soft skills (critical thinking, teamwork, communication) aligned with industry demands. Gamification significantly increases students' intrinsic motivation, self-efficacy, and engagement in career planning, facilitating more informed career decision-making and smoother transitions to the job market. The review identifies key implementation challenges, including high technological costs, limited digital literacy, and the need for faculty training. Despite these barriers, gamification demonstrates particular promise in diverse geographical contexts, from developed to developing countries, offering adaptable solutions for various institutional settings. This study contributes to the limited literature on gamification in career guidance by synthesizing current evidence and providing practical recommendations for higher education institutions seeking to systematically integrate gamified approaches into career curricula. Such integration, supported by cross-sector collaboration and attention to sociocultural factors, can enhance graduate employability and support lifelong learning in an increasingly competitive global workforce. Keywords: gamification, career guidance, employability, higher education, digital era, systematic literature review